Digital Marketing Efficiency and its Impact on the Financial Performance of Export SMEs in Central Java: A Digital Literacy Moderation Approach - Atmojo, Yustinus Dwi; Harmono, Pilipus Dwi; Hadi, Arman; Tanong, Mochtar; Sugiharti, Sugiharti (Journal of Economics and Public Health, 2024)
The development of digital technology has significantly impacted the marketing strategies of small and medium enterprises, particularly those engaged in export activities. This study aims to investigate the efficiency of digital marketing and its influence on the financial performance of export-oriented SMEs in Central Java, Indonesia, while also examining the moderating role of digital literacy. The research employs a quantitative approach, utilizing survey data collected from 200 export-focused SMEs in the region. The findings suggest that the effective implementation of digital marketing can positively impact the financial performance of these SMEs, with digital literacy serving as a critical moderator in strengthening this relationship. The study provides valuable insights for SME owners and policymakers in understanding the importance of digital marketing and digital literacy in enhancing the competitiveness and financial success of export-oriented businesses.